Biomechanical factors associated with running economy and performance of elite Kenyan distance runners: A systematic review. - Tawa, Nassib; Louw, Quinette (Journal of Bodywork & Movement Therapies, 2018)
Background Running economy (RE) is a determinant of performance in endurance sports and is a complex multi-factorial measure which reflects the combined functioning of bio-mechanical, neuro-muscular, metabolic and cardio-respiratory factors some of which are hereditary or adapt to coaching. Kenyan distance runners have dominated major global events with their unmatched performance for decades and this phenomenon has prompted several investigations aimed at establishing possible factors associated with their performance. This systematic review was aimed at establishing up-to date quantitative synthesis of evidence on biomechanical factors associated with running economy and performance of elite Kenyan distance runners and to provide an algorithm for future research and coaching strategies. Methods A comprehensive electronic search was conducted through June 2017. Quality appraisal was independently done by both reviewers using the STROBE checklist. Descriptive summaries and tables were used to illustrate biomechanical outcomes, mean differences and confidence intervals. Evidence from reviewed studies was graded according to the Australian National Health and Medical Research Council (NHMRC) hierarchy for aetiological factors and meta-analysis was performed where applicable. Results Eight cross-sectional studies were included. The overall methodological score was moderate (58%). Elite Kenyan distance runners have significant longer gastroc-Achilles tendons compared to their counterparts while their shank length is not significantly longer. There is no certainty of evidence regarding the association between their characteristic unique profile of tall and slender bodies, low BMI and low body mass, short ground contact and flight times, greater forward lean torso and faster and greater forward leg swing with RE and performance. Conclusion Our findings presents evidence on biomechanical factors associated with RE and performance of elite Kenyan distance runners. Despite these findings, there are a number of limitations inherent to this review including; low level of evidence, minimal number of included studies, small sample size and lack of appropriate control subjects. However, we considered these shortcomings and summarised the best available evidence in attempt to give direction to future research and coaching strategies.